Grid-connected CSI for hybrid PV/wind power generation system - Amorndechaphon D. (2017)
In this paper, the principle of a power conditioning unit for hybrid PV/wind power generation system is proposed. The proposed power conditioner is based on the current source inverter (CSI) topology. All energy sources are connected in parallel to a DC bus through the modified wave-shaping circuits. To achieve the unity power factor at the utility grid, the DC link current can be controlled via the wave-shaping circuits with the sinusoidal PWM scheme. The details of the operating principles and the system configurations are described and verified by the simulation results. © 2011 SICE.